DIFFERENCES OF CIRCUIT TRAINING WITH CONTROLLED SPEED POLYGON TOWARDS VO2MAX IN BKMF ATHLETIC BADMINTON FIK UNM - Zulfadli J; Saharullah Saharullah; Abdul Rahman (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2022)
The purpose of this study was to find out whether there was a difference between circuit training and Controled Speed Polygon against VO2Max in BKMF Badminton FIK UNM Athletes. The type of research used in this study was quantitative descriptive analysis. In this research design, research subjects were selected by purposive sampling. based on certain characteristics, research so that research subjects are homogeneous. While data analysis using SPSS 21 by using descriptive test, normality test and hypothesis testing. Based on the results of the analysis, the results of the difference in circuit training exercises with Controled Speed Polygon against VO2Max in BKMF Badminton FIK UNM Athletes obtained initial circuit training data against VO2Max in BKMF Badminton FIK UNM Athletes N (sample) 6 people, Mean 35.3000, T table value -5.170 and the value of sig.(2 tailed) 0.020 (p<0.05). This means that the initial data on circuit training training on VO2Max in BKMF Badminton FIK UNM athletes contributed, final data on circuit training training on VO2Max in BKMF Badminton FIK UNM Athletes N (sample) 6 people, Mean 38.3667, T table value -5.170 and sig.(2 tailed) 0.020 (p<0.05). means that the final data of circuit training on VO2Max at BKMF Badminton FIK UNM athletes contributed. And the end before and after doing circuit training got a value of 3.0667. and the final data of Controled Speed Polygon against VO2Max at BKMF Badminton FIK UNM N athletes (sample) 6 people, Mean 44.8167, T table value 0.305 and sig. (2 tailed) 0.029 (p<0.05). It means that the final data of Controled Speed Polygon Against VO2Max in BKMF Badminton FIK UNM Athletes contributed, and the data before and after doing circuit training got a value of -0.4.